A fiber-reinforced resin-based composite material and its preparation process
By treating the silane coupling agent on the surface of the glass fiber and using modified epoxy resin as the matrix resin, the problem of insufficient interface bonding of the fiber-reinforced resin matrix composite material is solved, and the mechanical properties and crack resistance of the material are significantly improved.
Patent Information
- Application Number
- CN202510060129.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-13
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
AI Technical Summary
The existing fiber-reinforced resin-based composite materials have weak interface bonds between glass fiber and resin matrix, which affects the overall performance and reliability of the material.
The surface of glass fibers is treated with silane coupling agent to form chemical reactions and form thin films to improve the interface bond between the fibers and the matrix. At the same time, a modified high-strength and high-toughness epoxy resin is used as the matrix resin to improve the bonding performance between the fiber and the matrix.
The interface bond between the fiber and the matrix is significantly improved, the mechanical properties and crack resistance of the composite material are improved, and a good flexible gradient layer is formed, reducing stress concentration on the interface layer.
Smart Images

Figure CN119775714A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber reinforced resin-based composite material production, and relates to a fiber reinforced resin-based composite material and a preparation process thereof. Background Art
[0002] Although fiber reinforced polymer (FRP) has many advantages, such as high strength, high stiffness, light weight, corrosion resistance, etc., it still has some shortcomings in practical applications. For example, the modulus between glass fiber and resin matrix is quite different, and the two are not easy to wet, resulting in weak interface bonding of the composite material, which greatly affects the overall performance and reliability of the material. Summary of the invention
[0003] In order to fill the gap in the prior art, the present invention provides a fiber-reinforced resin-based composite material and a preparation process thereof to overcome the deficiencies of the prior art.
[0004] The technical solution of the present invention:
[0005] A fiber-reinforced resin-based composite material comprises a reinforcing material with a content of 60-70% and a matrix resin with a content of 30-40%, wherein the reinforcing material is a carbon fiber cloth or a mixed cloth woven by mixing multiple fibers, and the matrix resin is a modified high-strength and high-toughness epoxy resin; the matrix resin comprises the following components in parts by weight: 100 parts of liquid epoxy resin, 10-30 parts of hyperbranched epoxy resin, 10-25 parts of epoxidized polybutadiene resin, 20-40 parts of epoxy reactive diluent, 0.3-1 part of epoxy curing agent, and 0.2-0.5 part of coupling agent.
[0006] Furthermore, the mixed fabric is a carbon fiber-glass fiber mixed fabric, a carbon fiber-aramid fiber mixed fabric or a high-strength basalt fiber-poly(p-phenylene benzobisoxazole) fiber mixed fabric.
[0007] Furthermore, the mixed cloth is a mixed cloth of high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber, the content of the basalt fiber is 60-75%, and the content of the bisoxazole fiber is 25-40%.
[0008] Furthermore, the liquid epoxy resin in the base resin is a hydrogenated bisphenol A type epoxy resin with a viscosity of 20000-25000mpa.s, the hyperbranched epoxy resin is a polyester type hyperbranched epoxy resin with a viscosity of 5000-8000mpa.s, the oxidized polybutadiene resin is a low-viscosity epoxidized polybutadiene resin with a molecular weight of 900-1200, the epoxy reactive diluent is one or a mixture of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, neopentyl glycol glycidyl ether, glycerol glycidyl ether, and trimethylolpropane glycidyl ether, the coupling agent is an epoxy group-containing silane coupling agent, and the epoxy curing agent is a modified amine with a viscosity of 1000-1500mpa.s.
[0009] A process for preparing any of the above-mentioned fiber-reinforced resin-based composite materials comprises the following steps:
[0010] S1, preparation of base resin, according to the weight ratio of 100 parts of liquid epoxy resin, 10-30 parts of hyperbranched epoxy resin, 10-25 parts of epoxidized polybutadiene resin, 20-40 parts of epoxy reactive diluent, 0.3-1 parts of epoxy curing agent, 0.2-0.5 parts of coupling agent, weigh each component, mix the liquid epoxy resin, hyperbranched epoxy resin, epoxidized polybutadiene resin, and epoxy reactive diluent, heat to 50-100°C, stir well for 30-50min, cool to below 50°C, add epoxy curing agent and coupling agent, stir well to obtain modified base resin;
[0011] S2. Preparation of reinforcing materials: selecting carbon fiber or multiple fibers for weaving into carbon fiber cloth or mixed cloth of multiple fibers;
[0012] S3, preparation of prepreg: placing the reinforcing material into the matrix resin for impregnation to obtain a fiber-reinforced epoxy resin prepreg;
[0013] S4. Preparation of composite materials: Cut the prepared fiber-reinforced epoxy resin prepreg and lay it in a mold at 110-160° C., press and cure it at a pressure of 5-10 MPa for 3-30 minutes to obtain a composite material.
[0014] Furthermore, in S2, the mixed fabric fibers are selected from carbon fiber-glass fiber, carbon fiber-aramid fiber or high-strength basalt fiber-poly(p-phenylene benzobisoxazole) fiber.
[0015] Furthermore, in S2, the mixed cloth is selected according to a content ratio of 60-75% of high-strength basalt fiber and 25-40% of bis(p-phenylene benzobisoxazole) fiber, and then the high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber are mixed and woven into a mixed cloth of high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber.
[0016] The beneficial effects of the present invention are:
[0017] (1) When the present invention uses a silane coupling agent to treat the surface of the glass fiber, the coupling agent is first hydrolyzed, and the glass fiber adsorbs the coupling agent from the solution to its surface, a chemical reaction occurs, and a film is formed. The epoxy coupling agent having a reactive functional group and the epoxy group in the epoxy resin matrix are used to treat the surface of the glass fiber, so that the interface bonding between the fiber and the matrix is significantly improved, thereby improving the comprehensive performance of the composite material. The epoxy group in epoxytrimethoxysilane can react with the epoxy group in the epoxy resin under the action of a curing agent. The coupling agent first reacts with the glass fiber, and after polycondensation, a silicon-oxygen bond is formed, so that the fiber is connected to the epoxy functional group, and then the epoxy functional group on the fiber reacts with the epoxy resin to form a polymer layer on the fiber. The composite interface is greatly improved, the connection between the fiber and the matrix is increased, and the interfacial bonding performance of the fiber-matrix is improved.
[0018] (2) The fiber and resin matrix at the fracture of the composite material of the present invention are well bonded, and the separation of the resin and the fiber is hardly seen at the interface between the fiber and the matrix, showing a strong anti-cracking ability. The mechanical properties of the composite material and the SEM analysis of the fracture surface show that the composite material produced by the process of the present invention can form a good flexible gradient layer on the interface, reduce and buffer the stress concentration on the interface layer, thereby comprehensively improving the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The fracture scanning electron microscope images of the composite material of the present invention and the composite material of the prior art are shown. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below.
[0021] Embodiment 1:
[0022] Preparation of composite materials:
[0023] S1. Preparation of matrix resin: Material category selection: Liquid epoxy resin shall select hydrogenated bisphenol A type epoxy resin with viscosity of 20000-25000mpa.s, hyperbranched epoxy resin shall select polyester type hyperbranched epoxy resin with viscosity of 5000-8000mpa.s, oxidized polybutadiene resin shall select low viscosity epoxidized polybutadiene resin with molecular weight of 900-1200, epoxy reactive diluent shall select mixture of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, neopentyl glycol glycidyl ether, propylene glycol glycidyl ether and trimethylolpropane glycidyl ether, coupling agent shall select silane coupling agent containing epoxy group, epoxy curing agent shall select modified amine with viscosity of 1000-1500mpa.s.
[0024] The components were weighed according to the weight ratio of 100 parts of liquid epoxy resin, 10 parts of hyperbranched epoxy resin, 10 parts of epoxidized polybutadiene resin, 20 parts of epoxy reactive diluent, 0.3 parts of epoxy curing agent and 0.2 parts of coupling agent. The liquid epoxy resin, hyperbranched epoxy resin, epoxidized polybutadiene resin and epoxy reactive diluent were mixed and heated to 50° C., stirred for 30 minutes, then cooled to below 50° C., epoxy curing agent and coupling agent were added and stirred evenly to obtain a modified base resin.
[0025] S2. Preparation of reinforcing material: selecting carbon fiber for weaving into carbon fiber cloth;
[0026] S3, preparation of prepreg: putting the reinforcing material carbon fiber cloth into the matrix resin for impregnation to obtain fiber reinforced epoxy resin prepreg;
[0027] S4. Preparation of composite materials: The prepared fiber-reinforced epoxy resin prepreg was cut and laid in a mold at 110° C., and pressed and cured at a pressure of 5 MPa for 30 minutes to obtain a composite material.
[0028] Embodiment 2:
[0029] Preparation of composite materials:
[0030] S1. Preparation of matrix resin: Material category selection: Liquid epoxy resin should be hydrogenated bisphenol A type epoxy resin with a viscosity of 20000-25000mpa.s, hyperbranched epoxy resin should be polyester type hyperbranched epoxy resin with a viscosity of 5000-8000mpa.s, oxidized polybutadiene resin should be low viscosity epoxidized polybutadiene resin with a molecular weight of 900-1200, epoxy reactive diluent should be 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, coupling agent should be silane coupling agent containing epoxy group, epoxy curing agent should be modified amine with a viscosity of 1000-1500mpa.s.
[0031] Weigh the components according to the weight ratio of 100 parts of liquid epoxy resin, 20 parts of hyperbranched epoxy resin, 18 parts of epoxidized polybutadiene resin, 30 parts of epoxy reactive diluent, 0.6 parts of epoxy curing agent and 0.35 parts of coupling agent, mix the liquid epoxy resin, hyperbranched epoxy resin, epoxidized polybutadiene resin and epoxy reactive diluent, heat to 75° C., stir for 40 minutes, cool to below 45° C., add epoxy curing agent and coupling agent and stir evenly to obtain a modified matrix resin;
[0032] S2. Preparation of reinforcing material: high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber are selected and mixed and knitted;
[0033] S3, preparation of prepreg: placing the reinforcing material into the matrix resin for impregnation to obtain a fiber-reinforced epoxy resin prepreg;
[0034] S4. Preparation of composite materials: The prepared fiber-reinforced epoxy resin prepreg was cut and laid in a 140° C. mold, and pressed and cured at a pressure of 7.5 MPa for 15 minutes to obtain a composite material.
[0035] Embodiment 3:
[0036] Preparation of composite materials:
[0037] S1. Preparation of base resin:
[0038] Material category selection: Liquid epoxy resin uses hydrogenated bisphenol A type epoxy resin with a viscosity of 20000-25000mpa.s, hyperbranched epoxy resin uses polyester type hyperbranched epoxy resin with a viscosity of 5000-8000mpa.s, oxidized polybutadiene resin uses low viscosity epoxidized polybutadiene resin with a molecular weight of 900-1200, epoxy reactive diluent uses a mixture of neopentyl glycol glycidyl ether, propylene glycol glycidyl ether and trimethylolpropane glycidyl ether, and the mass ratio of neopentyl glycol glycidyl ether, propylene glycol glycidyl ether and trimethylolpropane glycidyl ether is 3-5:1-2:3-5, coupling agent uses epoxy group-containing silane coupling agent, epoxy curing agent uses modified amine with a viscosity of 1000-1500mpa.s.
[0039] Weigh the ingredients according to the weight ratio of 100 parts of liquid epoxy resin, 30 parts of hyperbranched epoxy resin, 25 parts of epoxidized polybutadiene resin, 40 parts of epoxy reactive diluent, 1 part of epoxy curing agent, and 0.5 parts of coupling agent, mix the liquid epoxy resin, hyperbranched epoxy resin, epoxidized polybutadiene resin, and epoxy reactive diluent, heat to 100° C., stir well for 50 minutes, cool to below 40° C., add epoxy curing agent and coupling agent, stir well to obtain a modified matrix resin;
[0040] S2. Preparation of reinforcing material: Select carbon fiber-glass fiber or carbon fiber-aramid fiber for mixing to prepare carbon fiber-glass fiber mixed cloth and carbon fiber-aramid fiber mixed cloth respectively, the content ratio of carbon fiber to glass fiber is 10:90-90:10, and the content ratio of carbon fiber-aramid fiber is 10:90-90:10;
[0041] S3, preparation of prepreg: placing the reinforcing material into the matrix resin for impregnation to obtain a fiber-reinforced epoxy resin prepreg;
[0042] S4. Preparation of composite materials: The prepared fiber-reinforced epoxy resin prepreg was cut and laid in a 160° C. mold, and pressed and cured at a pressure of 10 MPa for 30 minutes to obtain a composite material.
[0043] Embodiment 4:
[0044] The performance test analysis of the composite material of the present invention:
[0045] (1) Composite material fracture test analysis:
[0046] Figure 1 The composite material morphology of the fracture of the carbon fiber reinforced epoxy composite material of the present invention is shown in FIG. 1. From the fracture morphology, it can be seen that the fracture morphology of the glass fiber surface and the resin matrix of the composite material in the prior art is relatively smooth, showing a brittle fracture.
[0047] The composite material resin matrix of the present invention is bonded to the surface of the carbon fiber to form a coating layer with a dense structure and uniform thickness, and the rupture of the composite material occurs between the coating layer and the matrix resin. Not only is a large amount of resin coated on the surface of the fiber, but also a dimple-shaped cross-section similar to the resin matrix is formed, indicating that the interface bonding between the fiber and the matrix is very excellent. The fiber and matrix interface in the composite material of the prior art is relatively smooth, indicating that the ability of the fiber-matrix interface to withstand stress is poor. Under the action of stress, many micro-debonding phenomena occur between the fiber and matrix interface, affecting the strength of the material. The fiber and resin matrix at the fracture of the composite material of the present invention are well bonded, and it is difficult to see the separation phenomenon of the resin and the fiber at the interface of the fiber and the matrix, showing a strong anti-cracking ability. The mechanical properties of the composite material and the fracture SEM analysis show that the composite material of the present invention can form a good flexible gradient layer on the interface, reduce and buffer the stress concentration on the interface layer, thereby comprehensively improving the mechanical properties of the composite material.
[0048] (2) Bending performance test
[0049] The mechanical properties of composite materials depend on the properties of the reinforcing material and the resin matrix and the bonding between them. Under the action of external load, the reinforcing material plays the main role of bearing the load, while the matrix material generally only plays the role of transmitting the shear stress between the fibers and preventing the fiber from buckling. The interfacial bonding between the two directly determines the mechanical properties of the composite material. The better the bonding between the fiber and the matrix, the more uniform the distribution of the applied load between the fibers, and the better the mechanical properties of the composite material.
[0050] Since composite materials are subject to large loads during use, their bending performance is very important and is one of the basic indicators for evaluating the performance of the sheet. The bending performance of composite materials is very sensitive to the type, performance and molding process parameters of raw materials. Therefore, the bending performance of composite materials can also consider the selection of raw materials and the quality of molding processes to a certain extent. The main focus is on the bending strength and modulus in the normal and hot vertical layers.
[0051] Mechanical properties test, using R-4050 electronic universal testing machine, the maximum range is 50kN. Bending performance is measured according to GB / T1449, the test loading rate is 10mm / min. Tensile properties are measured according to GB / T1447, the test loading rate is 5mm / min. Interlaminar shear strength is measured according to GB / T1450.1, the test loading rate is 2mm / min Shenzhen Rigel production. The test results are shown in Table 1 below. From the test results, it can be seen that the mechanical properties of the composite material of the present invention have exceeded the same type of composite materials currently on the market.
[0052] Table 1 Bending performance test results
[0053]
[0054] (3) Impact performance test
[0055] When composite materials are subjected to dynamic loads, the impact strength (toughness) performance index of composite materials is required. The impact strength also indicates the toughness of the material and is one of the performance indicators for material selection. The test method is the impact strength of a simply supported beam with a notch parallel to the layer. The simply supported beam impact test is conducted using an XJJ-50 simply supported beam impact testing machine with a maximum impact energy of 50J. The impact test is measured according to GB / T1451. Produced by Chengde Puhui Testing Instrument Manufacturing Co., Ltd.
[0056] The parallel layer impact strength of the composite material is shown in Table 2. It can be seen from the table that the parallel layer impact strength of the composite material tested by the simply supported beam notch method shows that the impact performance of the composite material meets the requirements. It can be seen from the table that the difference in impact strength of each part of the composite material is within an acceptable range.
[0057] Table 2 Impact strength
[0058]
[0059] (4) Compression performance test:
[0060] The compressive strength test results of the composite material are shown in Table 3. It can be seen from the table that the average perpendicular layer compressive strength is 447Mpa, and the average parallel layer compressive strength is 302Mpa, which fully meets the requirements.
[0061] Table 3 Compressive strength of composite materials
[0062] performance Parallel to layer Vertical layer Compression strength, MPa 302 447
[0063] (5) Load deformation temperature test
[0064] The load heat deformation temperature (HDT) is the temperature corresponding to the specified deformation when a certain load is applied to a polymer or polymer and the temperature is increased at a certain speed. It is a measure of the heat resistance of polymers or polymer materials. HDT is one of the main indicators for measuring the heat resistance of resin-based composite materials. It refers to the temperature when a certain size of rectangular resin sample immersed in a heat-conductive liquid medium heated at a heating rate of 2℃ / min is applied with a specified load, and the deformation of the midpoint of the sample reaches a specified value corresponding to the height of the sample. The heat deformation temperature values determined by different load values are different and not comparable.
[0065] HDT reflects the maximum working temperature of the material, especially for load-bearing structural materials. If the temperature is higher than HDT, the deformation of the material will increase sharply. The test results are shown in Table 4. It can be seen that the load heat deformation temperature (HDT) of the composite material of the present invention is as high as 250°C or more, and its performance far exceeds that of the same type of composite materials currently on the market.
[0066] Table 4 Load deformation temperature test
[0067]
[0068] (6) Flame retardant performance test:
[0069] The role of insulating composite materials determines that they must have good flame retardant properties. Generally, when polymer materials are heated in the air, they will decompose to generate volatile combustibles. When the concentration of combustibles and the system temperature are high enough, they can burn. Whether the ignited polymer material can continue to burn after the ignition source is stabilized depends on the heat balance of the combustion process. When the heat generated by the combustion is equal to or greater than the total heat required in each stage of the combustion process, the polymer material can continue to burn, otherwise it will be stopped or extinguished. From the combustion mechanism of polymer materials, it can be seen that the essence of flame retardancy is achieved by slowing down or preventing one or several factors.
[0070] The flame retardant test results are shown in Table 5. The flame retardant performance of the composite material of the present invention reaches V0 level through comprehensive judgment of the first ignition extinguishing time, the total extinguishing time of the sample, and the second ignition extinguishing time. The flame retardant performance of the V0 level flame retardant material shows the highest flame retardant performance in the test.
[0071] Table 5 Flame retardant properties
[0072] Test method Vertical combustion First ignition off time, s 5,6,8,4,7 Second ignition off time, s 20,18,25,22,27 Result determination V0
[0073] The above shows and describes the basic principles, main features and advantages of the present invention. The present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A fiber-reinforced resin-based composite material, characterized in that: The invention comprises a reinforcing material with a content of 60-70% and a matrix resin with a content of 30-40%, wherein the reinforcing material is a carbon fiber cloth or a mixed cloth woven by mixing multiple fibers, and the matrix resin is a modified high-strength and high-toughness epoxy resin; the matrix resin comprises the following components in parts by weight: 100 parts of liquid epoxy resin, 10-30 parts of hyperbranched epoxy resin, 10-25 parts of epoxidized polybutadiene resin, 20-40 parts of epoxy active diluent, 0.3-1 parts of epoxy curing agent, and 0.2-0.5 parts of coupling agent.
2. A fiber-reinforced resin-based composite material according to claim 1, characterized in that: The mixed fabric is a carbon fiber-glass fiber mixed fabric, a carbon fiber-aramid fiber mixed fabric or a high-strength basalt fiber-poly(p-phenylene benzobisoxazole) fiber mixed fabric.
3. A fiber-reinforced resin-based composite material according to claim 2, characterized in that: The mixed cloth is a woven cloth mixed with high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber, the content of the basalt fiber is 60-75%, and the content of the bisoxazole fiber is 25-40%.
4. A fiber-reinforced resin-based composite material according to claim 1, characterized in that: The liquid epoxy resin in the base resin is a hydrogenated bisphenol A type epoxy resin with a viscosity of 20000-25000 mpa.s, the hyperbranched epoxy resin is a polyester type hyperbranched epoxy resin with a viscosity of 5000-8000 mpa.s, the oxidized polybutadiene resin is a low-viscosity epoxidized polybutadiene resin with a molecular weight of 900-1200, the epoxy active diluent is one or a mixture of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, neopentyl glycol glycidyl ether, glycerol glycidyl ether, trimethylolpropane glycidyl ether, the coupling agent is a silane coupling agent containing an epoxy group, and the epoxy curing agent is a modified amine with a viscosity of 1000-1500 mpa.s.
5. A process for preparing a fiber-reinforced resin-based composite material according to any one of claims 1 to 4, characterized in that: The steps include: S1, preparation of base resin, according to the weight ratio of 100 parts of liquid epoxy resin, 10-30 parts of hyperbranched epoxy resin, 10-25 parts of epoxidized polybutadiene resin, 20-40 parts of epoxy reactive diluent, 0.3-1 parts of epoxy curing agent, 0.2-0.5 parts of coupling agent, weigh each component, mix the liquid epoxy resin, hyperbranched epoxy resin, epoxidized polybutadiene resin, and epoxy reactive diluent, heat to 50-100°C, stir well for 30-50min, cool to below 50°C, add epoxy curing agent and coupling agent, stir well to obtain modified base resin; S2. Preparation of reinforcing materials: selecting carbon fiber or multiple fibers for weaving into carbon fiber cloth or mixed cloth of multiple fibers; S3, preparation of prepreg: placing the reinforcing material into the matrix resin for impregnation to obtain a fiber-reinforced epoxy resin prepreg; S4. Preparation of composite materials: Cut the prepared fiber-reinforced epoxy resin prepreg and lay it in a mold at 110-160° C., press and cure it at a pressure of 5-10 MPa for 3-30 minutes to obtain a composite material.
6. The process for preparing the fiber-reinforced resin-based composite material according to claim 5, characterized in that: In S2, the mixed fabric fibers are selected from carbon fiber-glass fiber, carbon fiber-aramid fiber or high-strength basalt fiber-poly(p-phenylene benzobisoxazole) fiber.
7. The process for preparing a fiber-reinforced resin-based composite material according to claim 6, characterized in that: In S2, the mixed cloth is selected according to the content ratio of 60-75% of high-strength basalt fiber and 25-40% of bisoxazole fiber, and then the high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber are mixed to form a mixed cloth of high-strength basalt fiber and poly(p-phenylene benzobisoxazole) fiber.
Citation Information
Cited By
Glass fiber reinforced plastic composite material resistant to chlorine salt freezing and thawing, preparation method and application of glass fiber reinforced plastic composite material in preparation of water taking head
CN120137354A